Problem granic trzynastowiecznych kasztelanii górnośląskich na przykładzie księstwa opolskiego : próba bilansu - Woźny, Maciej (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The article aims to summarize the research on the problem of borders of the castellanies within the Duchy of Opole at the end of the 13 th conducted so far. The author presents the most important conclusions stemming from the discussion in historiography, and analyzes which of the attempts and methods of outlining these borders have been proven false. The previous research supports the opinion that in light of the current state of knowledge on sources, these borders cannot be precisely established.
Keywords: kasztelanie; granice; Górny Śląsk; księstwo opolskie